Friction coefficients for stainless steel (PTFE) teflon bearings - Stanton, John F.; Taylor, Josef C. (Wisconsin Highway Research Program, 2010)
This report describes a study on sliding bridge bearings made from PTFE and stainless steel. Such bearings are commonly made from sheet PTFE and stainless steel polished to a #8 mirror finish. That surface finish is the only one for which the AASHTO LRFD Design Specifications provide design values of the friction coefficient. However, it can be expensive and difficult to obtain. The objective of the work was to determine the suitability of stainless steel with a 2B surface finish in sliding bearings. 2B stainless steel is produced by cold rolling and is not polished. It is thus more readily available and less expensive, but it has a rougher finish. A program of tests was undertaken to investigate the coefficient of friction and the wear characteristics of sliding bearings. Three stainless steel surface finishes were used: #8 mirror (as a reference), 2B, and a rough hot-rolled finish that was initially supplied by the Wisconsin Department of Transportation. The results of the tests were analyzed and recommendations were prepared. Friction between PTFE and a hard material such as stainless steel varies with many parameters, the most important of which are: surface finish, contact pressure, sliding speed, slide path and temperature. The first four of these were addressed in the tests; low temperature testing requires special equipment that lay outside the scope of the project. The test results shared many characteristics with those found in previous studies. Static, or breakaway, friction is higher than sliding friction. The coefficient of friction is sensitive to contact pressure (unlike, for example, steel on steel, for which it is essentially independent of contact pressure), and increases at low pressure. It increases as sliding speed increases, although, within the range of sliding speeds expected in a non-seismic application, the sensitivity is not great. By contrast, the effects of slide path were unexpected. For the mirror finish material, the coefficient of friction rose with increasing slide path, for the rough hot-rolled material, it fell, and for the 2B material it remained almost constant, even over one very long slide path test of three-quarters of a mile. At the end of each long slide-path test, the mirror finish material almost always displayed the highest friction coefficient. This result was counter-intuitive, but was consistent across essentially all tests with the three materials. Wear of the PTFE was also measured, and was found to be very low for the 2B finish. A general equation was developed from the test data with which to predict the friction coefficient as a function of surface finish, contact pressure, sliding speed and slide path. Computations were done to estimate the slide path demand in a real bridge. It was found to vary greatly among bridges, and to depend on column stiffness, span length, superstructure type and details, and temperature profile. 2B surface finish stainless steel displayed stable and relatively low friction properties, based on which it was deemed to be a suitable alternative to #8 mirror finish, subject to the caveat that its performance characteristics at low temperature are unknown.
125 p.
Keywords: Coefficient of friction; Wear; Stainless steel; Laboratory tests; Polytetrafluoroethylene; Bridge bearings